2021
DOI: 10.3390/ani11051346
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Implications of the Complete Absence of Guests on a Zoo-Housed Gorilla Troop

Abstract: Research conducted on the effects that zoo visitors have on primate behavior has yielded inconsistent patterns. This study aims to contribute to the growing body of literature regarding visitor effects on zoo-housed primate’s activity budgets, with the purpose of quantifying the behavioral variability under two conditions: guest presence and guest absence. Due to the COVID-19 pandemic, many zoos were closed to the public for varying lengths of time. The Buffalo Zoo was closed to guests for an 18-week period in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
(39 reference statements)
2
13
3
Order By: Relevance
“…Overall, however, most studies conducted during COVID-19 closures reported entirely or mainly neutral effects that suggest a minimal impact from visitors. There were no significant differences in behavior between the closures and open periods reported for western lowland gorillas (Gorilla gorilla gorilla) [19], African penguins [16], greater flamingos (Phoenicopterus roseus) [18], Amur leopards (Panthera pardus orientalis), snow leopards (Panthera uncia), Rothschild giraffes (Giraffa camelopardalis), Chapman's zebras (Equus quagga chapmani), nyala (Tragelaphus angasii), swamp wallabies (Wallabia bicolor) [20], Eastern black-and-white colobus, Allen's swamp monkeys, DeBrazza's monkeys, Bolivian gray titi monkeys, or crowned lemurs [12]. Additionally, Nile crocodiles [10], greater and Chilean flamingos [18], Amur leopards, snow leopards, Rothschild giraffes, Chapman's zebras, nyala, swamp wallabies, and Chinese gorals (Naemorhedus griseus) [20] showed no difference in space use between open and closed periods.…”
Section: Introductionmentioning
confidence: 72%
“…Overall, however, most studies conducted during COVID-19 closures reported entirely or mainly neutral effects that suggest a minimal impact from visitors. There were no significant differences in behavior between the closures and open periods reported for western lowland gorillas (Gorilla gorilla gorilla) [19], African penguins [16], greater flamingos (Phoenicopterus roseus) [18], Amur leopards (Panthera pardus orientalis), snow leopards (Panthera uncia), Rothschild giraffes (Giraffa camelopardalis), Chapman's zebras (Equus quagga chapmani), nyala (Tragelaphus angasii), swamp wallabies (Wallabia bicolor) [20], Eastern black-and-white colobus, Allen's swamp monkeys, DeBrazza's monkeys, Bolivian gray titi monkeys, or crowned lemurs [12]. Additionally, Nile crocodiles [10], greater and Chilean flamingos [18], Amur leopards, snow leopards, Rothschild giraffes, Chapman's zebras, nyala, swamp wallabies, and Chinese gorals (Naemorhedus griseus) [20] showed no difference in space use between open and closed periods.…”
Section: Introductionmentioning
confidence: 72%
“…Cognitive performance on touch screen memory tests of Japanese macaques (Macaca fuscata) showed no difference in participation rates or accuracy between open versus closed conditions, but there were significantly faster response latencies when the zoo was open [25]. Six western lowland gorillas (Gorilla gorilla gorilla) showed no group behavioral differences when a zoo was open versus closed; however, there were individual differences [50]. For example, auto-grooming occurred in 12% of observed behaviors of the silverback in 2019, when the zoo was open, and was not observed in 2020 when the zoo was closed.…”
Section: Introductionmentioning
confidence: 92%
“…The initial wave of the SARS-CoV-2 (COVID-19) pandemic in early 2020 forced zoos to close for the first prolonged period of time in the United States (U.S.) and globally. Since then, several visitor effect studies of various zoo-housed taxa have been published due to the unique opportunity these closures provided [17,[25][26][27][49][50][51][52][53]. Greater flamingos (Phoenicopterus roseus) showed no behavioral changes between the open and closed conditions, while Chilean flamingos (P. chilensis) showed a decrease in three out of eight observed behaviors (activity, movement, and feeding) when the zoo reopened; however, these changes were partially attributed to weather [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zoo visitors have often been found to have adverse effects on zoo animal behavior (e.g., [268][269][270]), but not necessarily for all species [271]. In one study of a group of captive gorillas in a zoo in the USA, the total absence of zoo visitors as a consequence of the pandemic lockdown produced no substantive effect on animal behavior [272]. Similar results were found in observations of the behavior of several species at zoos in Ireland and the United Kingdom [65].…”
Section: Protecting the Welfare Of Animals In Zoos And Aquariumsmentioning
confidence: 99%